PENGUATAN KAPASITAS KELEMBAGAAN BUMDES SEJAHTERA BERSAMA DESA NYATNYONO KABUPATEN SEMARANG - Nafilatun Nafichah, Rifka; Zarkasyi Rahman, Amni (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The institutional capacity building serves as a key reference for improving organisational performance, including BUMDes Sejahtera Bersama, an economy-based community organisation in Nyatnyono Village, Semarang Regency. Following Government Regulation No. 11 of 2021 on BUMDes, BUMDes Sejahtera Bersama strives to revitalise its institutional capacity to achieve the goal of empowering the local economy in Nyatnyono Village. However, this effort faces challenges related to the misalignment of stakeholder interests in managing its business units. This study aims to describe the institutional capacity of BUMDes Sejahtera Bersama within the context of Nyatnyono Religious Tourism Village. Using a qualitative approach, the primary data source was obtained through interviews. The data analysis process involved several stages: description, reduction, selection, and conclusion. Atlas.TI software supported data analysis by facilitating the visualization of findings. The results reveal a detailed description of BUMDes Sejahtera Bersama's institutional capacity and the factors influencing it. Recommendations from this study include enhancing collaboration with third parties, strengthening external oversight, and reinforcing social capital.